Integration of Economic and Social Values of the Ecosystem Services of the Miguel Lillo Park (Necochea, Argentina) - Guerrero, Elsa Marcela (2019)
The Miguel Lillo Park is a public forestall system of local importance that provides ecosystem services and has economic and socio-cultural values for the city. The article identifies and values the main ecosystem services of the Park physically, economically and socio-culturally. The method of environmental modeling is used to characterize the forest ecosystem and identify the services to be assessed. Chrematistic values are determined for the CO2 sequestration capacity and existence value, and a qualitative matrix is applied to determine the socio-cultural value of the park. Integrating different value systems is a methodological challenge not always easy to overcome in the search for a measure of the total value of the environmental benefits provided by ecosystems. It is possible to estimate a monetary value of the park of 35 000 USD, visibly undervalued, a figure slightly higher than the budget allocated to the Secretary of Planning and Environment (23 000 USD), equivalent to 0, 16 % of the total annual budget of the Municipality of Necochea for the year 2016.